Studying the Kitab of Nashoihul Ibad in Improving the Practice of Prayer in Islamic Boarding Schools - Hasbunallah, Hasbunallah; Muhith, Abdul; Usriyah, Lailatul (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The focus of this research is 1) how is the material for reciting the Nashoihul Ibad book in increasing the practice of prayer in the community of Parasgowang Hamlet 2) how is the use of the method of reciting the Nashoihul Ibad book in increasing the practice of prayer in the community of Parasgowang Hamlet 3) how is the use of the media reciting the Nashoihul Ibad book in increasing the practice of worship the prayer of the people of Parasgowang Hamlet. This research uses a type of descriptive qualitative research approach with a case study type of research. The techniques used in collecting data are interviews, observation, and documentation. Based on the results of the research, it can be concluded that after the community understands the material presented in the process of reciting the book Nashoihul Ibad, the community tries to increase solemnity in prayer services, and always to always stay away from prohibitions and obey His commands. Furthermore, the method used in the process of reciting the Nashoihul Ibad book is the bandongan and sorogan method, but the demonstration method is also used for some materials that are required for practice. Finally, the media used in the recitation process is printed media in the form of the Nashoihul Ibad book.